Transmission of Acceleration from a Synchronous Vibration Exercise Platform to the Head - Caryn, R. C.; Hazell, T. J.; Dickey, J. P. (International Journal of Sports Medicine, 2014)
Exercise vibration platforms are becoming commonplace in homes and fitness centers. However, excessive mechanical energy transferred to the head and eye can cause injury. The purpose of this study was to evaluate how changes in platform frequency and knee flexion angle affect acceleration transmission to the head. Participants (N=12) stood on a whole-body vibration platform with knee flexion angles of 0°, 20°, and 40° to evaluate how changes in knee flexion affected head acceleration. 7 specific platform frequencies were tested between 20–50 Hz at 2 peak-to-peak displacement settings (1 and 2 mm nominal). Accelerations were measured with triaxial accelerometers at the platform and head to generate transmissibility ratios. Platform-to-head transmissibility was not significantly different between the 2 platform peak-to-peak amplitudes (P>0.05). Transmissibility measures varied depending on platform frequency and knee angle (P < 0.05). Flexing the knees resulted in reduced head transmissibility at all frequencies (P<0.05). Platform-to-head transmissibility values exceeded 1.0 at both 20 and 25 Hz platform vibration frequencies with the knees in full extension. To reduce the risk of injury to structures of the head during vibration exercise, using platforms frequencies below 30 Hz with small knee flexion angles (< 40°) should be avoided.
Keywords: resonance; knee flexion; standing